ANALISIS KESALAHAN BERBAHASA TULIS PEBELAJAR BAHASA INDONESIA UNTUK PENUTUR ASING (BIPA) DI SANGGAR KAMPUNG INDONESIA TULUNGAGUNG - Mohamad Jazeri (Jurnal Bahasa Lingua Scientia, 2013)
This research is intended to describe the errors in writing text in Bahasa Indonesia made by BIPA (Bahasa Indonesia for Foreign Speakers) learners in Kampung Indonesia Tulungagung which encompass (1) phonological, morphological, syntactical, and semantical errors and (2) the factors causing those errors made by the learners of BIPA.. The data are the learners’ writing in their diary and the final task after the teaching process. Those writing is then analyzed based the linguistic taxonomy which includes the errors in phonology, morphology, syntax, and semantics. The data analysis technique used is flow analysis model. The steps of analysis are (1) collecting data, (3) identifying the errors, (4) grading the errors, (5) analyzing the errors, (6) correcting the errors, and (7) discussing the errors. The findings of this research shows that (a) the language errors in phonology is 43.2%, (b) the language errors in morphology is 25.4%, (c) the language errors in syntax is 24.1%, (d) the language errors in semantic is 7.3%.Those language errors are caused by two factors: the internal and external factors. The internal factors include (a) low motivation, (b) different potential, (c) interference, and (d) the closeness of language group or family. The external factors include (a) incomplete teaching and learning process, and (b) the short period of teaching process.